Implementation of Islamic Religious Education Courses at the Center for the Implementation of Personality Formation Courses (PP-MPK) Universitas Sriwijaya, Indonesia - Sri Safrina (Manunggal Halim Jaya, 2024)
Islamic religious education has an important role in shaping the character and morals of students in higher education. The implementation of religious education aims to create a generation that is not only intellectually intelligent, but also has strong moral and spiritual integrity. In Indonesia, the implementation of religious education is strengthened by Law of the Republic of Indonesia Number 12 of 2012 concerning Higher Education. The method in this research uses qualitative methods with content analysis techniques. This student character formation course aims to instill noble values and build strong personalities in students. The implementation of learning material is carried out face-to-face in lecture classes and through e-learning. Islamic Religious Education at PP-MPK Sriwijaya University is a mandatory course which aims to equip students with a broad knowledge base, develop critical thinking skills, and shape student character. This course covers various topics related to Islamic teachings and is implemented through face-to-face, virtual face-to-face and via e-learning methods. The implementation of Islamic religious lectures is not only carried out in the classroom but is also carried out at the Al Ghazali Mosque on the Palembang and Indralaya campuses. In addition to promoting activities at the campus mosque, this activity aims to put into practice the learning of the theory that has been obtained in the classroom, so that students can later put it into practice. learning outcomes into the real world.